Lean quality improvement model for quality practices in software industry in Pakistan. Issue 4 (6th April 2015) - Shah, Faisal Tehseen; Shamail, Shafay; Ahmad Akhtar, Niaz
Abstract Implementation of quality and achieving quality culture in small and medium software houses (SMSH) have been a subject of discussion among the industry. The existing software process improvement frameworks are too heavy for SMSH. There is a need of lean quality models that will help SMSH in establishing quality culture with minimal effort and resources. The objective of this research study is to map the environment and culture of SMSH in Pakistan towards quality improvement and process improvement by implementing total quality management philosophy. A lean quality improvement model (LQIM) consisting of four quality constructs and 10 quality practices has been proposed. The LQIM is validated using good fit indices in structural equation modeling. At the end, implementation of the proposed LQIM is explained using the Deming's philosophy of plan, do, check, act cycle for continuous process improvement. Copyright © 2015 John Wiley & Sons, Ltd.